1998
DOI: 10.1046/j.1523-1755.1998.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia decreases calcium influx into rat proximal tubules

Abstract: Renal ischemia results in adenosine triphosphate (ATP) depletion, particularly in cells of the proximal tubule (PT), which rely heavily on oxidative phosphorylation for energy supply. Lack of ATP leads to a disturbance in intracellular homeostasis of Na+, K+ and Cl-. Also, cytosolic Ca2+ levels in renal PTs may increase during hypoxia [1], presumably by a combination of impaired extrusion and enhanced influx [2]. However, Ca2+ influx was previously measured using radiolabeled Ca2+ and at varying partial oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Previous studies have found that TRPV6 and CaBP-9k appear to be involved in calcium absorption [63,68,83] or reabsorption [65,84]. Similar to a previous investigation [85], we observed reduced calcium influx in the proximal tubules of the kidney after urine calcium levels were increased by hypoxia. Our results demonstrated that calcium is not reabsorbed in the kidney with hypoxic stress and is excreted in the urine.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have found that TRPV6 and CaBP-9k appear to be involved in calcium absorption [63,68,83] or reabsorption [65,84]. Similar to a previous investigation [85], we observed reduced calcium influx in the proximal tubules of the kidney after urine calcium levels were increased by hypoxia. Our results demonstrated that calcium is not reabsorbed in the kidney with hypoxic stress and is excreted in the urine.…”
Section: Discussionsupporting
confidence: 91%
“…Incidentally, reduced Ca 2 þ permeability has also been reported in hypoxic kidney tubules, where it was ascribed a protective role. 26 In contrast to the permanent inactivation of the PMCA by thiol modification 27 or proteolytic cleavage, 11 the fall in PMCA activity early during stress was reversible. Resistance of the PMCA and other Ca 2 þ pumps to hydrogen peroxide has been reported earlier, 25,28 which for the PMCA is conferred by calmodulin.…”
Section: Discussionmentioning
confidence: 99%
“…Probenecid has been used as a pharmacological tool in many different experimental settings next to renal transport inhibition, e.g. in measurements of intracellular pH ( Weinberg et al ., 1994 ) and free Ca 2+ ( Ruttner et al ., 1993 ; Peters et al ., 1998 ), and cell volume control ( Kanli & Terreros, 1997 ). In the first two experimental conditions probenecid was used in millimolar concentrations to retain intracellularly loaded fluorophores.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, probenecid has been widely used in high concentrations (up to 10 m M ) as a pharmacological tool to retain intracellularly loaded anionic fluorophores, such as pH indicators ( Weinberg et al ., 1994 ) and calcium probes ( Ruttner et al ., 1993 ; Peters et al ., 1998 ). In addition to a direct interaction with transport, it may also be possible that the inhibition of dye ‘leakage’ by probenecid is mediated at a different level.…”
Section: Introductionmentioning
confidence: 99%